1992
DOI: 10.1111/j.1442-200x.1992.tb00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Sound Spectrographic Studies on the Relation Between Motherese and Pleasure Vocalization in Early Infancy

Abstract: The relationship between the vocalizations of early infants and their mothers was investigated by acoustic analysis. The subjects were eight infants aged 40–70 days and their mothers. The infants were sufficiently developed to utter pleasure vocalization. The acoustic characteristics of the voices of the infants and mothers while communicating with each other analyzed in terms of pitch, duration, latency and melody types. The results were as follows: 1) Correlation was significant between the average fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…One study (Beebe, Alson, Jaffe, Feldstein & Crown, 1988) found a correlation across mother–infant dyads in the duration of response times at turns, but not of within-speaker pauses. Both this study and another (Shimura & Yamanoucho, 1992) found no correlation in the durations of infant and mother utterances.…”
Section: Introductioncontrasting
confidence: 73%
See 1 more Smart Citation
“…One study (Beebe, Alson, Jaffe, Feldstein & Crown, 1988) found a correlation across mother–infant dyads in the duration of response times at turns, but not of within-speaker pauses. Both this study and another (Shimura & Yamanoucho, 1992) found no correlation in the durations of infant and mother utterances.…”
Section: Introductioncontrasting
confidence: 73%
“…Similarly, McRoberts and Best (1997), examining a single infant longitudinally from 3 to 17 months, found adjustment in the form of higher pitch by the mother and father when speaking with their infant (as would be expected either because of general characteristics of infant-directed speech or because of an entrainment effect) but no difference in the infant's mean pitch depending on whether the infant was alone, with mother, or with father across the age range. Shimura and Yamanoucho (1992) found correlations both between and within mother–infant dyads with respect to mean pitch for 2- to 3-month-olds, but did not attempt to disentangle mother–infant or infant–mother effects. One study, Masataka (1992), found that 3- to 4-month-old infants showed significantly more similarity to their mother in the intonation contours of their vocalizations in response to exaggerated intonation on the part of their mother.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers may also match their pitch to infants’ vocalizations. In the first 3 months, IDS and infants’ vocalizations are correlated in pitch, and even melody types are correlated in some mother-infant pairs [59] with tonal synchrony [60]. This correlation may be due to the parents, given that, in a longitudinal case study, parents consistently adjusted their vocal patterns to their 3- to 17-month-old infants’ vocal patterns, whereas infants did not adjust their vocal patterns to their parents’ vocal patterns [61].…”
Section: Resultsmentioning
confidence: 99%
“… 63 Likely genetic, motherese is more than a speech style; it is a tool for reciprocal engagement that enhances social and language development, with infants often matching the fundamental frequencies and voice pitch of their mothers. 64 Using gaze-contingent eye tracking that allowed toddlers to control the images and sounds they heard, we found that similar to toddlers who are typically developing or non–ASD delayed, the majority of toddlers with ASD attended to motherese speech at high levels. In contrast, approximately 23% of toddlers with ASD showed low levels of attention toward motherese speech, with some as low as 1% to 2%.…”
Section: Discussionmentioning
confidence: 94%
“…The animated speech style known as motherese can be found across cultures and languages, is evident between deaf mothers and their deaf children, and has even been noted to occur while fetuses are still in the womb . Likely genetic, motherese is more than a speech style; it is a tool for reciprocal engagement that enhances social and language development, with infants often matching the fundamental frequencies and voice pitch of their mothers . Using gaze-contingent eye tracking that allowed toddlers to control the images and sounds they heard, we found that similar to toddlers who are typically developing or non–ASD delayed, the majority of toddlers with ASD attended to motherese speech at high levels.…”
Section: Discussionmentioning
confidence: 99%